Kerangka Dasar Penyusunan dan Penyajian Laporan Keuangan Syariah - Ilyas, Rahmat (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Islamic transactions based on the basic paradigm that the universe was created by God as amanah (trust Divine) and means the joy of life for all mankind to prosper materially and spiritually intrinsic (Al-falah). The basic paradigm emphasizes every human activity has accountability and divine values that put the sharia and morals as parameters of good and bad, right and wrong with the business activity. Financial reporting is the structure and process of accounting that describes how the financial information provided and reported to achieve the goal of economic and social state